2022
DOI: 10.7717/peerj.13710
|View full text |Cite
|
Sign up to set email alerts
|

ZmIAA5 regulates maize root growth and development by interacting with ZmARF5 under the specific binding of ZmTCP15/16/17

Abstract: Background The auxin indole-3-acetic acid (IAA) is a type of endogenous plant hormone with a low concentration in plants, but it plays an important role in their growth and development. The AUX/IAA gene family was found to be an early sensitive auxin gene with a complicated way of regulating growth and development in plants. The regulation of root growth and development by AUX/IAA family genes has been reported in Arabidopsis, rice and maize. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The functions of 15 of the 29 Aux/IAA gene families in Arabidopsis have been clearly reported (Yang F et al, 2022). For example, Arabidopsis plants with the acquired mutant iaa8, of the Aux/IAA gene family, were found to have shorter heights, loss of apical dominance, frizzled leaves, and abnormal flower organ development (Reed JW, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The functions of 15 of the 29 Aux/IAA gene families in Arabidopsis have been clearly reported (Yang F et al, 2022). For example, Arabidopsis plants with the acquired mutant iaa8, of the Aux/IAA gene family, were found to have shorter heights, loss of apical dominance, frizzled leaves, and abnormal flower organ development (Reed JW, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that AUX/IAA proteins and auxin-responsive factor (ARF) mediated signaling play an important role in regulating plant root formation (Yang F et al,2022). ZmIAA10 can interact with ZmARF25 and ZmARF34, thereby affecting root growth and development in maize (Deng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations